3D Printing of Thermoplastic‐Bonded Soft‐ and Hard‐Magnetic Composites: Magnetically Tuneable Architectures and Functional Devices. (6th September 2019) - Chatzipirpiridis, George; Gervasoni, Simone; Fischer, Cedric; Ergeneman, Olgaç; Pellicer, Eva; Nelson, Bradley J.; Pané, Salvador
Abstract : Magnetic materials are key players for the development and implementation of novel technologies. However, the integration and tunability of these materials in complex designs remain challenging due to constraints in currently available manufacturing approaches. Herein, the fabrication of 3D printing (3DP) thermoplastic‐bonded magnetic composites is investigated with both tailored geometries and magnetic properties using a customized fused deposition modeling 3D printer. First, the level of complexity that can be achieved by printing magnetic architectures with different geometries is shown. Next, it is shown that architectures with tailored magnetic properties (saturation magnetization and coercivity) can be achieved by combining prints with different magnetic properties (i.e., hard‐ and soft, or hard‐ and semi‐hard). Additionally, to demonstrate the versatility and powerfulness of fused deposition, self‐contained mechanisms, which comprise multiple parts (magnetic and nonmagnetic) without the need for assembly, are successfully fabricated. As an example, planetary magnetic gearboxes are printed with different configurations and their potential applicability as magnetic rotary encoders is demonstrated. Abstract : Magnetic materials are key players for the development and implementation of novel intelligent systems. Herein, the fabrication of 3D‐printed magnetic polymer composites with both tailored geometries and magnetic properties is investigated. Self‐contained mechanisms, which comprise multiple parts (magnetic and nonmagnetic) without the need for assembly, such as planetary gearboxes, are successfully fabricated.